Reconstruction of radial deviation after preaxial polydactyly surgery: use of an ulnar fascial flap - Chen, Hua; Wu, Kang; Wang, Hongrui; Hu, Yong; Wang, Yang (Frontiers in Pediatrics, 2024)
Background: Radial deviation of the interphalangeal (IP) joint is a common complication of treating Wassel type IV-D preaxial polydactyly. Long-term radial deviation can place excessive tension on the radial skin and cause overabundance of the ulnar skin. To overcome this problem, we aimed to utilize a fascial flap for ulnar reconstruction of a defect in the radial skin. Methods: We used a fascial flap for ulnar reconstruction of a defect in the radial skin, eight patients (average: 12 years, range: 5-33 years) who underwent reconstructive surgery at our department for radial deviation of the interphalangeal (IP) joint after the initial operation were included between August 2017 and August 2021. An incision was made on the radial side of the thumb. An olive-shaped flap was designed on the ulnar eminence of the IP joint. The skin and fascia in the other three quadrants were incised. While the flap was protected, children with epiphyseal plates underwent wedge osteotomy at the maximum ulnar deviation of the proximal phalanx, and adults underwent direct fusion of the distal IP joint. Absorbable sutures were used to suture the flap. The Tada functional and visual analog scale (VAS) scores were recorded before and after the operation.Results: All flaps survived without infection or necrosis. The preoperative and postoperative Tada scores were 1 and 5, respectively, and the preoperative and postoperative VAS scores were 3 and 9, respectively. The postoperative scores showed a statistically significant degree of improvement.Conclusions: An ulnar fascial flap is an effective and feasible option for repair of radial deviation following surgery for preaxial polydactyly.